Alarm reaction depends on multiple chemical cues in tadpoles of the cane toad (Rhinella marina). Issue 3 (4th May 2023) - Hemnani, Mahima; Guimarães, Izabela S. Campos; Kaefer, Igor L.; Pires, Tiago H. da Silva
Abstract : Early detection of predators is fundamental for the survival of the prey. Predator detection can occur by perception of the chemical substances released by predators or injured conspecifics, granting prey the opportunity to avoid the attack. However, overreacting to cues can generate false alarm reactions that result in fruitless energetic costs. Given that chemical cues in natural habitats rarely occur singly, individuals can benefit from obtaining information from multiple sources, such as the combined chemical cues from predators and conspecifics. We experimentally tested the movement reaction of cane toad ( Rhinella marina ) tadpoles when in contact with isolated chemical cues from a conspecific, a predator (dragonfly larvae), and the combination of these two substances. We quantified duration of swimming activity before and after the exposure to the chemical cues and compared it to a control group. A significant reduction in swimming activity was only observed when the tadpoles were exposed to the combination of both cue types. Our results suggest that the tadpoles can recognise the chemical cues from conspecifics and predators, but a behavioural response is only elicited when both stimuli are detected simultaneously. We suggest that behavioural change in response to predation threat in R. marina is a compromise between early detection of predators and avoidance of unnecessary energetic expenditures.